Socio-Economic Factors and Access to Palliative Care Services to Chronically Ill Patients in Industrial City Division Mbale City - Nandudu Sandra (Uganda Christian University, 2024)
The study was guided by the topic socio-economic factors and access to palliative care services to chronically ill patients in Industrial City Division, Mbale City. The study was guided by the following research objectives: To find out the effect of income levels on access to palliative care services by chronically ill patients in Industrial City Division Mbale City, to investigate the effect of education levels on access to palliative care services by chronically ill patients in Industrial City Division Mbale City and lastly to examine the effect of religion on access to palliative care services by chronically ill patients in Industrial City division Mbale City. The study used both a qualitative and quantitative research design where it considered a population of 100 respondents which give rise to a sample size of 80 respondents. The study findings revealed that: that many patients have continued to depend largely on external funding for palliative care as most of these service consumers are poor and poorest of the poor, that palliative care services have not been utilized due to poverty of most patients and their families, that patients with low levels of education often presented themselves for palliative care at the advanced stage of their illness and this accounted for complications and poor quality of life, that patients with low educational attainments are not aware of available palliative care services, that patients who are deeply religious had a high level of palliative care services uptake compared to non-religious and lastly that religious belief system and sociocultural backgrounds are obstacles which affect the provision of palliative care services. The study findings concluded that: Many patients have continued to depend largely on external funding for palliative care as most service of these services consumers are poor and poorest of the poor, that palliative care services have not been utilized due to poverty of most patients and their families and that access to palliative care among the poor is low due to high cost of palliative care services, that patients with low levels of education often present themselves for palliative care at the advanced stage of their illness and this accounted for complications and poor quality of life. The study recommended that there is more need to invest in palliative care services in different areas in the country in order to ensure effective service delivery and lastly that there is need to change people's sociocultural backgrounds which are obstacles in provision of palliative care services.